2019
DOI: 10.1167/iovs.19-27162
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Receptor Expression Pattern Correlates to Progression of Conjunctival Melanocytic Lesions

Abstract: Citation: van Ipenburg JA, de Waard NE, Naus NC, Jager MJ, Paridaens D, Verdijk RM. Chemokine receptor expression pattern correlates to progression of conjunctival melanocytic lesions. Invest Ophthalmol Vis Sci. 2019;60:2950-2957. https://doi.org/ 10.1167 PURPOSE. Chemokines play a role in the progression and metastatic spread of both cutaneous and uveal melanomas. The aim of this study was to examine the prognostic value of expression of chemokine receptors CCR7, CXCR4, and CCR10 in conjunctival melanocytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Next, the percentage of stained cells that showed the predominant intensity, was determined; no positive cells were scored as 0% and less than 10%, 10% to 50%, 51% to 80%, and more than 80% were scored as 1, 2, 3, or 4, respectively. Then, IRS was calculated by multiplying the score for percentage of stained cells with the score for the intensity of the staining [41].…”
Section: Abhd6 Immunohistochemistrymentioning
confidence: 99%
“…Next, the percentage of stained cells that showed the predominant intensity, was determined; no positive cells were scored as 0% and less than 10%, 10% to 50%, 51% to 80%, and more than 80% were scored as 1, 2, 3, or 4, respectively. Then, IRS was calculated by multiplying the score for percentage of stained cells with the score for the intensity of the staining [41].…”
Section: Abhd6 Immunohistochemistrymentioning
confidence: 99%
“…For these stainings an immunoreactive score (IRS) was determined as has been described in a previous report. 13 First, intensity of the staining was classified as absent (0), mild (1), moderate (2) or intense (3). Secondly, percentage of stained cells that showed the predominant intensity was scored as no positive cells (0), less than 10% (1), 10% to 50% (2), 51% to 80% (3), and more than 80% (4).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that an outgrowth of lymphatic vessels is concomitant with the development of CM, possibly due to the increased expression of lymphangiogenic and chemotactic factors at the invasive edge of CM [ 30 , 31 , 32 ]. This mechanism could also explain the migration to and invasion of CM cells into the lymphatic vessels [ 33 , 34 ]. This prolymphangiogenic potential does not seem to be only associated with CM cells, but could also involve cells present in the TME [ 35 ].…”
Section: Biology Of Conjunctival Melanomamentioning
confidence: 99%